Altitudinal variation of secondary metabolite profiles in flowering heads of Arnica montana cv. ARBO - Spitaler, R.; Schlorhaufer, P.D.; Ellmerer, E.P.; Merfort, I.; Bortenschlager, S.; Stuppner, H.; Zidorn, C.
The altitudinal variation on the contents of secondary metabolites in flowering heads of Arnica montana was assessed. Plants of A. montana cultivar ARBO were grown in nine experimental plots at altitudes between 590 and 2230 m at Mount Patscherkofel near Innsbruck/ Austria. The total contents of sesquiterpene lactones and flavonoids were not positively correlated with the altitude of the growing site. However, the roportion of flavonoids with vicinal free hydroxy groups in ring B to flavonoids lacking this feature significantly increased with elevation. Additionally, the level of caffeic acid derivatives also positively correlated with the altitude of the growing site. In particular amounts of 1-methoxyoxaloyl-3,5-dicaffeoylquinic acid significantly increased in higher sites and samples from the summit region contained 85
Keywords: ARNICA MONTANA; ALTITUDINAL EFFECTS; CHEMICAL ECOLOGY; PHENOLICS; CAFFEIC ACID ESTERS; SESQUITERPENE LACTONES; NATURAL PRODUCTS; UV RADIATION